Watershed Management: A Rational Approach to Producing, Conserving, and Sustaining Natural Resources - Ffollion, Peter F; Brooks, Kenneth N (Annals of Arid Zone, 2016)
A watershed management approach to land stewardship accommodates the interests of the widest possible number of people. The approach examines the benefits obtained from land stewardship by optimizing production and maintaining environmental integrity. It also facilitates more effective conflict resolution from a sustainability perspective. The approach further recognizes that future generations of people deserve to inherit landscapes that are capable of producing the needed goods and services while maintaining ecosystem health and economic stability. How watershed management is implemented to conserve and sustain the flow of high quality water, wood production and other forestry activities, livestock production, and agricultural cropping and to mitigate effects ofland use on soil erosion, sedimentation, and flooding is the focus of this paper. Cumulative watershed effects that might not be apparent at any particular location or time, but when viewed in a downstream perspective can have significant impacts on 'people living downstream for a longer time period are also addressed. Institutional and policy considerations are discussed to place watershed management into a proper perspective.